Comparison of Intraoperative Bleeding During Bilateral Endoscopic Sinus Surgery with or without Greater Palatine Fossa Block - Pokharel, Apar; Panta, Basanta (Journal of College of Medical Sciences-Nepal, 2024)
Background Functional endoscopic sinus surgery (FESS) is a minimally invasive technique commonly used to restore sinus ventilation and function under direct visualization. A small amount of bleeding can obscure the surgical field. Block of greater palatine fossa (GPF) through the greater palatine foramen via trans-oral approach may be used as technique for controlling bleeding during FESS. The objective of this study is to see the study the effect of GPF block on intraoperative bleeding during endoscopic sinus surgery. Methods This was a quasi experimental study was conducted on 34 patients undergoing surgery in COMS-TH, Bharatpur, Chitwan during a period of 1 year. Unilateral Trans Oral infiltration of the GPF with 2 mL of 2% lidocaine and 1:80,000 adrenalin was done, and other side was infiltrated with normal saline. Results In our study, the endoscopic surgical field grade between normal saline and 2 mL of 2% lidocaine and 1:80,000 adrenaline suggested that GPF block group has significantly lesser bleed than saline infiltrated side. Conclusions In our study, the GPF block group maintained a lower surgical grade during the entire duration of surgery when compared to normal saline.